Applicability of the Guide for Monitoring Child Development as a Telehealth Delivered Intervention During the Pandemic - Ozalp Akin, Ezgi; Akbas, Aysen; Atasoy, Sidika Canan; Kanatli, Merve Cicek; Ince Acici, Selin; Mustafayev, Revan; Karaaslan, Bedriye Tugba; Ertem, Hilmi Deniz; Bingoler Pekcici, Bahar; Ertem, Ilgi (Frontiers in Pediatrics, 2022)
Background: Early intervention delivered through telehealth is critically needed during crises, particularly for children in low and middle-income countries (LMICs). We aimed to determine the applicability of the international Guide for Monitoring Child Development (GMCD) intervention delivered through telehealth during the COVID-19 lockdown in Turkey. Methods: Using a mixed-methods longitudinal design, we recruited children with developmental difficulties aged 0-42 months with an appointment during the first lockdown at Ankara University Developmental Pediatrics Division (AUDPD) and seen face-to-face only once before. Developmental pediatricians applied the GMCD intervention during a single telephone call. As a novel intervention component, caregivers were asked to record and send back videos of the child’s development when there were doubts about the child’s functioning. Caregivers were called one year later by blinded independent researchers and a semi-structured interview on applicability was conducted. Applicability of the caregiver recorded video component of the intervention was assessed by a blinded observer using the GMCD Video Observation Tool. Results: Of 122 children that received the telehealth delivered GMCD intervention, 114 (93.4%) were included in the one-year outcome study. Most were boys (51.8%); median age was 16.5 (IQR: 10.0-29.0) months, 51.0% had chronic health conditions, and 66.7% had developmental delay. All caregivers that received the intervention were mothers; 75.4% had at least high school education. The intervention was reported as applicable by 80.7% with high levels of satisfaction. On multivariate regression analysis, absence of chronic health related conditions was significantly associated with applicability (OR= 2.87, 95% CI=1.02-8.09). Of 31 caregivers that were asked for videos, 19 sent back 93 videos that were technically observable. One or more developmental domains were observed in all videos; in 52.6% caregivers provided early learning opportunities. Conclusions: The findings of this study imply that the telehealth delivered GMCD intervention for children with developmental difficulties is applicable during the pandemic. The intervention content and frequency needs to be augmented for children with chronic health conditions. Further research is required to examine applicability and effectiveness of the GMCD intervention in other settings, particularly in LMICs.